2013
DOI: 10.1007/s00467-013-2562-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seasonal variation on blood pressure measurements in children, adolescents and young adults

Abstract: Blood pressure measurements in children and adolescents, even in a temperate climate, are influenced by temperature and subject to seasonal variation. Considering seasonal variations in blood pressure could be of clinical interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 20 publications
3
27
0
Order By: Relevance
“…Estimated overall SBP/DBP changes from summer to winter were 2.28/1.24 mm Hg in T1DM patients and 2.48/0.64 mm Hg in T2DM patients, at differences in a mean outdoor temperature of approximately 18°C. These changes were lower than those reported in Japanese (approximately 25°C yearly temperature differences), Taiwanese (subtropical monsoon climate, Chinese (various temperate zones), and Iraqi (hot summer season) adult study cohorts, but comparable to results observed in studies with similar climatic conditions . A German study in both healthy and sick children and adolescents aged 3 to 21 years reported an SBP decrease of 0.12 mm Hg with each 1°C increase in outdoor temperature, which corresponds to our estimation.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Estimated overall SBP/DBP changes from summer to winter were 2.28/1.24 mm Hg in T1DM patients and 2.48/0.64 mm Hg in T2DM patients, at differences in a mean outdoor temperature of approximately 18°C. These changes were lower than those reported in Japanese (approximately 25°C yearly temperature differences), Taiwanese (subtropical monsoon climate, Chinese (various temperate zones), and Iraqi (hot summer season) adult study cohorts, but comparable to results observed in studies with similar climatic conditions . A German study in both healthy and sick children and adolescents aged 3 to 21 years reported an SBP decrease of 0.12 mm Hg with each 1°C increase in outdoor temperature, which corresponds to our estimation.…”
Section: Discussionsupporting
confidence: 77%
“…These changes were lower than those reported in Japanese (approximately 25°C yearly temperature differences), Taiwanese (subtropical monsoon climate, Chinese (various temperate zones), and Iraqi (hot summer season) adult study cohorts, but comparable to results observed in studies with similar climatic conditions . A German study in both healthy and sick children and adolescents aged 3 to 21 years reported an SBP decrease of 0.12 mm Hg with each 1°C increase in outdoor temperature, which corresponds to our estimation. It was previously proposed that, paradoxically, seasonal BP differences are lower in countries with cold winters than in countries with mild winters, possibly attributable to better thermal efficiency standards leading to more constant indoor temperature .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our study showed that BP decreased from baseline to post-intervention in both the CG and IG, which aligned with two previous intervention trials conducted by Almas et al [28] and Seo et al [29]. A previous study suggested that BP measurement underwent a seasonal variation or influenced by outdoor temperature [30]. The BP of our study was assessed in October and June, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Even repeated BP measures on several occasions (clinic visits) may not provide an accurate assessment of a patient's BP, as the BP changes with daytime/nighttime period, level of stress and anxiety, surrounding temperature, seasons [13] and other factors. Home BP monitoring offers a more reliable BP assessment than the office BP measurement, and this strategy has also been proven to be feasible in children and adolescents, resulting in the development of appropriate reference values [14].…”
Section: Bp Levels In Adults and Childrenmentioning
confidence: 98%